The general and his daughter : the wartime letters of General James M. Gavin to his daughter Barbara - Gavin, James M. (James Maurice), 1907-1990 (World War II--the global, human, and ethical dimension., 2007)
James Maurice Gavin left for war in April 1943 as a colonel commanding the 505th Parachute Infantry Regiment of the 82nd Airborne Division?America?s first airborne division and the first to fight in World War II. In 1944, ?Slim Jim? Gavin, as he was known to his troops, at the age of thirty-seven became the 82nd?s commanding general?the youngest Army officer to become a major general since the Civil War. At war?s end, this soldier?s soldier had become one of our greatest generals?and the 82nd?s most decorated officer.Now James Gavin?s letters home to his nine-year-old daughter Barbara provide a revealing portrait of the American experience in World War II through the eyes of one of its most dynamic officers. Written from ship decks, foxholes, and field tents?often just before or after a dangerous jump?they capture the day-to-day realities of combat and Gavin?s personal reactions to the war he helped to win. And provide an invaluable self-portrait of a great general, and a great American, in war and peace.The book?s more than 200 letters begin at Fort Bragg in 1943 and continue to December 1945, as Gavin came home to lead the 82nd at the head of the Victory parade in New York. This correspondence constitutes the majority of Gavin?s private wartime letters, but except for rare appearances in regimental newsletters, it has never before been published. In her Introduction, Epilogue, and Notes, Barbara Gavin Fauntleroy gives a privileged glimpse of the private man. Edited by Gayle Wurst, the book features historical overviews by Starlyn Jorgensen, a preface by noted Gavin biographer Gerard M. Devlin, and a foreword by Rufus Broadaway, Gavin?s aide-de-camp.